Teachers’ perceptions on the concept of Murabbi in Islamic integrated schools in Zanzibar - Malengo, Faki Ali; Md. Noon, Hazizan (2017)
This study sought to understand the meaning and application of the concept of Murabbi in teaching and learning process among the teachers in Islamic Integrated Schools in Zanzibar. Three male and three female teachers from these schools were selected as respondents. Semi-structured in-depth interview was employed for primary data collection while secondary data were solicited from relevant documents such as journal articles, textbooks, official reports and proceedings. The findings of this study showed that all respondents were of the opinion that teachers’ responsibility should go beyond normal teaching duties to embrace the task of looking after and taking care of the students as practically is reflected in their actual works that covered also the non-typical teaching tasks. The study thus recommended that further investigation be conducted to further explore the understanding and application of the concept of murabbi among teachers of all Integrated Islamic Schools in Zanzibar especially through quantitative-based research.